Observer-based synchronization of fractional-order Markovian jump multi-weighted complex dynamical networks subject to actuator faults - Sakthivel, R.; Sakthivel, R.; Kwon, O.M.; Selvaraj, P. (Journal of the Franklin Institute, 2021)
This paper is concerned with an observer-based robust H∞ synchronization problem for a class of fractional-order multi-weighted complex dynamical networks subject to Markovian jump parameters, actuator faults and time-varying coupling delay by using fault-tolerant control scheme. The considered actuator fault model is a general one, which consisting of both linear and nonlinear fault terms. Further, by employing a continuous frequency distributed equivalent model and using indirect Lyapunov approach, a new set of sufficient conditions is derived to ensure the asymptotic synchronization of the addressed system in the mean square sense with a prescribed H∞ performance index. In particular, by constructing monochromatic Lyapunov functional and utilizing extended Wirtinger-based integral inequality the required sufficient conditions are developed in terms of linear matrix inequalities. Finally, two numerical examples including financial model are provided to illustrate the effectiveness of the obtained results.